Zn-Fe Double Hydroxide-Carbon Nanotube Anodes for Asymmetric Supercapacitors - Liang, Wenyu; Zhitomirsky, Igor (Frontiers in Materials, 2020)
Zn-Fe double hydroxide (Zn-Fe-DH) – multiwalled carbon nanotube (MWCNT) composite has been developed for energy storage in negative electrodes of asymmetric supercapacitors. A conceptually new approach is based on the use of celestine blue (CB) dye as a multifunctional additive. We discovered that CB acted as a dispersant for Zn-Fe-DH and MWCNT, facilitated their mixing and interfacial charge transfer. The electrodes showed a capacitance of 5.2 F cm-2 in 0.5 M Na2SO4 electrolyte in a voltage window of -1.0 - -0.2 V vs saturated calomel electrode and good cyclic stability. A new asymmetric device has been developed, containing Zn-Fe-DH-MWCNT negative electrodes and polypyrrole coated MWCNT positive electrodes. Good capacitive behaviour of cathode and anode materials was achieved at high active mass of 40 mg cm-2 in partially overlapping potential windows. The device showed promising performance in a voltage window of 1.6 V. The capacitance of 2.2 F cm-2 was obtained at a scan rate of 2 mV s-1.